got wil uns hail geben, das man uns der latein zu deutsch pring: Das Werk des Österreichischen Bibelübersetzers - Popst, Nadine (Vulgata in dialogue, 2023)
The so called ‘Austrian Bible Translator’ is an anonymous, non-ordained translator in the first half of the 14th century. Some 200 years before Martin Luther, he strove to give people with no knowledge of Latin the opportunity to read and understand the Bible in their own language. His identity is unknown. He wrote several tracts, but it is his Bible translations and commentaries that mark a milestone in the history of vernacular Bible translations. This paper offers a first overview of his work, his aims and working techniques.